2013
DOI: 10.1039/c3ra44192j
|View full text |Cite
|
Sign up to set email alerts
|

Bis(4′-(4-pyridyl)-2,2′:6′,2′′-terpyridine)ruthenium(ii) complexes and their N-alkylated derivatives in catalytic light-driven water oxidation

Abstract: Hydrogen sulfate salts of [Ru(1) 2 ] 2+ where 1 ¼ 4 0-(4-pyridyl)-2,2 0 :6 0 ,2 00-terpyridine and four N-alkylated derivatives [Ru(L) 2 ] 4+ were used as photosensitizers (l max $510 nm) for water oxidation in light driven reactions with peroxydisulfate as a sacrificial electron acceptor and Na 10 [Co 4 (H 2 O) 2 (a-PW 9 O 34) 2 ] (Co 4 POM) as the catalyst in sodium borate buffers at pH 8.0 and 9.0. The N-substituents investigated were benzyl (L + ¼ 2 +), ethyl (L + ¼ 3 +), allyl (L + ¼ 4 +) and 4-cyanobenzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Buffer-dependent WOC performance was furthermore found to increase in the order carbonate z phosphate [ borate, despite the higher stability of [Ru(bpy) 3 ] 2+ in borate compared to phosphate media. 68,69 Recycling tests with CoNCN. Catalyst recycling experiments at pH 9 upon addition of fresh carbonate buffer solution and PS/ electron acceptor, respectively, resulted in a reactivation of WOC performance by ca.…”
Section: Esi †)mentioning
confidence: 99%
“…Buffer-dependent WOC performance was furthermore found to increase in the order carbonate z phosphate [ borate, despite the higher stability of [Ru(bpy) 3 ] 2+ in borate compared to phosphate media. 68,69 Recycling tests with CoNCN. Catalyst recycling experiments at pH 9 upon addition of fresh carbonate buffer solution and PS/ electron acceptor, respectively, resulted in a reactivation of WOC performance by ca.…”
Section: Esi †)mentioning
confidence: 99%
“…Compounds similar to the methylated complexes 3 and 4 , i. e., N ‐alkylated 4’‐pyridyl substituted terpyridine ruthenium complexes, were previously studied as photosensitizers in photocatalytic water oxidation. These studies showed that the N‐alkylated bis‐terpyridine complexes can lead to a comparable oxygen evolution activity as the standard ruthenium tris‐bipyridine PS [5j] …”
Section: Discussionmentioning
confidence: 99%
“…5.5, 34 0.02 and 0.05 s À1 in borate buffer at pH 8 and 9, respectively. 35,36 This is for a generic reaction (eqn (2)) where one or more of the bpy ligands are oxidized one or more times; some of the bpy ligand is fully oxidized to CO 2 , however, the products are largely [Ru(bpy) 3 ] 2+ with the yield up to 98% based on initial Ru 3+ . Sutin et al have identified at least eight separate products in previous work.…”
Section: Simplified Reaction Mechanismmentioning
confidence: 99%